Contractual and Entrepreneurial Freedom, and Its Tension with the Prohibition on Outsourcing Core Business Activities - Moscoso Becerra, Gerson (2025)
The present article aims to argue that the prohibition on outsourcing services linked to the core of the business infringes upon the formal scope of the employer’s constitutional rights to freedom of contract and freedom of enterprise. This infringement arises from the failure to assess the nature of outsourcing as a mechanism of business collaboration and from disregarding the binary nature of managerial authority. Such violations materialize through state intervention generated by the enactment of Supreme Decree No. 001-2022-TR. For this reason, managerial authority will be analyzed as a constitutional right of a binary nature, capable of optimization in outsourcing contexts, in order to demonstrate that the prohibition on outsourcing services collides with the content of contractual and entrepreneurial freedom. Finally, the action of amparo against an implementing regulation is proposed as the appropriate mechanism to protect the employer’s constitutional rights infringed by the regulation.